Harry Potter: Konsumsi dan Pemujaan Komoditas Dunia Sihir (Kajian Media dalam Perspektif Marxis) - Malau, Ruth (Jurnal The Messenger, 2013)
Harry Potter, the book and film series are form of celebration of the magic world commodities. Media then took place as an amplifier that bringing the magic worlds as a part embodied in our real world. Magic commodity consumption turns out with a magically success. Youth in different parts of world named themself as the generation of Harry Potter. The existance of Harry Potter has become a fetishism consumption, but activated so many Marxism critique about inequality and materialism, while consuming and celebrating the cultural industry of Harry Potter.